Analysis of the Antigenic Composition and Differential Incorporation of Host Membrane Proteins into Murine Leukemia Virus by Flow Virometry - Maltseva, Mariam (Université d'Ottawa / University of Ottawa, 2020)
Traditionally, viral particles have been primarily analyzed as a whole population according to their biochemical, genetic, and biophysical properties. Here, we describe single particle phenotypic analysis using surface markers found on Murine Leukemia Virus (MLV) by flow virometry. We used this technology to show differential incorporation of host surface markers between wild type MLV and glycosylated Gag (glycogag) deficient MLV. Moreover, we analyzed differential uptake efficiency of host proteins between two cell lines and primary lymphocytes. We hypothesize that the phenotypic profiling and quantification of antigens on the surface of individual viral particles will provide crucial information on the identity of the infected parental cells. Furthermore, we demonstrate that the MLV accessory protein glycogag is associated with the upregulation of surface antigen incorporation during assembly and release. Aside from possible evolutionary implications of glycogag, we demonstrate presence and varying antigenic composition on the surface of MLV viral particles reflective of the cell phenotype that they were released from.
Keywords: Virology; Retroviruses; Flow Cytometry; Flow Virometry; HIV; MLV